2007
DOI: 10.1021/bi700974t
|View full text |Cite
|
Sign up to set email alerts
|

DNA Recognition via Mutual-Induced Fit by the Core-Binding Domain of Bacteriophage λ Integrase

Abstract: Bacteriophage lambda integrase (lambda-Int), a phage-encoded DNA recombinase, cleaves its substrate DNA to facilitate the formation and later resolution of a Holliday junction intermediate during recombination. The core-binding and catalytic domains of lambda-Int constitute a bipartite enzyme that mediates site-specific DNA cleavage through their interactions with opposite sides of the recognition sequence. Despite minimal direct contact between the domains, the core-binding domain has been shown to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, upon complex formation the entire N-terminus becomes ordered, as its residues exhibit large NOE values similar to amino acids in the remainder of the domain. Interestingly, other parts of the Int protein also undergo DNA induced folding as recent studies have shown that the core domain is poorly structured in its free form, but folds upon binding to DNA 19.…”
Section: Introductionmentioning
confidence: 99%
“…However, upon complex formation the entire N-terminus becomes ordered, as its residues exhibit large NOE values similar to amino acids in the remainder of the domain. Interestingly, other parts of the Int protein also undergo DNA induced folding as recent studies have shown that the core domain is poorly structured in its free form, but folds upon binding to DNA 19.…”
Section: Introductionmentioning
confidence: 99%